In vitro evaluation of antimicrobial properties of a new Mannich base N-[(Diphenylamino)methyl]acrylamide and its Oxovanadium(IV), Cerium(IV), Thorium(IV) and Dioxouranium(VI) metal chelates against human pathogenic microorganisms - Muruganandam, L; Balasubramanian, K; Krishnakumar, K; Venkatesa Prabhu, G (Journal of Experimental Sciences, 2013)
N-[(Diphenylamino)methyl]acrylamide(DPAMAcry) was synthesized using Mannich reaction and its complexes of oxovanadium(IV), cerium(IV), thorium(IV) and dioxouranium(VI) were prepared and characterized by elemental analysis, UV, IR and EPR spectral studies. All the newly synthesized compounds have been screened for their antibacterial and antifungal activities. All of them show promising antibacterial and antifungal activity.